Association Between Smoking and Hypertension in Pregnancy Among Japanese Women: A Meta-analysis of Birth Cohort Studies in the Japan Birth Cohort Consortium (JBiCC) and JECS - Naho Morisaki; Taku Obara; Aurelie Piedvache; Sumitaka Kobayashi; Chihiro Miyashita; Tomoko Nishimura; Mami Ishikuro; Fumihiro Sata; Reiko Horikawa; Chisato Mori; Hirohito Metoki; Kenji J Tsuchiya; et al. (Journal of Epidemiology, 2023)
Background: Recent literature suggest the effect of maternal smoking on risk of hypertensive disorders in pregnancy (HDP) and preeclampsia may differ by ethnicity; however, studies on Asians are limited. Methods: We investigated the association of maternal smoking with HDP and preeclampsia using a common analysis protocol to analyze the association in six birth cohorts participating in a Japanese consortium of birth cohorts (JBiCC). Results were compared with-published results from cohorts not included in this consortium, and, where possible, we produced a meta-analysis including these studies. Results: Meta-analysis of four cohort studies including 28,219 participants produced an odds ratio (OR) of 1.24 (95% confidence interval [CI], 0.88–1.87) for the effect of smoking beyond early pregnancy compared to women who did not smoke during pregnancy. These results combined with those from the Japan Environment and Children’s Study (JECS) yielded an OR of 1.19 (95% CI, 1.00–1.43, P = 0.056). Meta-analysis results for categories of smoking volume were insignificant, but when combined with JECS yielded an OR of 0.86 (95% CI, 0.65–1.12) for smoking 1–4 cigarettes, 1.25 (95% CI, 0.98–1.60) for smoking 5–9 cigarettes, and 1.27 (95% CI, 1.04–1.54) for smoking 10 or more cigarettes per day. All effects were insignificant for preeclampsia. Conclusion: Our results suggest that the protective effects of smoking longer and smoking more on HDP and preeclampsia repeatedly observed among Europeans and North Americans likely do not hold for the Japanese.